Lyrics training como uma ferramenta tecnológica para potencializar o ensino e aprendizado da língua inglesa - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
This research investigates the impact of Lyrics Training, an app and website, on developing listening skills in English classes. The goal is to assess whether technology can enhance the listening abilities of non-native students, particularly Portuguese speakers, who face challenges such as pronunciation differences and sounds that don’t exist in Portuguese, like the “th” in “think” and “bath,” as well as varied accents, speed, and intonation in speech. Digital Information and Communication Technologies (DICTs) are tools that facilitate English learning by automating and optimizing the educational process. Consisting of devices such as computers and digital whiteboards, DICTs, especially the internet, have become accessible and are part of students’ daily lives, supporting education through new resources. Using these technologies in school settings can ease difficulties in studying the language, as they help develop the four language skills: reading, listening, speaking, and writing. For native Portuguese speakers, these skills are acquired naturally, but English learning requires auditory training. This study highlights listening as an essential skill for understanding phrases and sounds in English. Music is an effective resource for enhancing this skill, and Lyrics Training can be a useful tool in this regard, aiding in auditory comprehension and contributing to fluency development.
Lyrics training as a technological tool for enhancing english language teaching and learning
Keywords: Listening; Tecnologia; Ensino-aprendizagem - Língua inglesa; Lyrics Training; Listening; Technology; English language teaching and learning; CIENCIAS HUMANAS::EDUCACAO; ENSINO-APRENDIZAGEM::TECNOLOGIA EDUCACIONAL